2002
DOI: 10.1038/sj.dmfr.4600715
|View full text |Cite
|
Sign up to set email alerts
|

A new device for measuring density of jaw bones.

Abstract: Normal human bone density is 1.85 (g/cm(3)), and this densitometer is useful for determination of material densities from 1.304 (g/cm(3)) to 1.882 (g/cm(3)). The device may be useful for precise bone density assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
13
0
4
Order By: Relevance
“…Jaw bone densitometry studies were found to be far more accurate when including a fiduciary reference object, such as a step wedge, in the image. Some of these include an aluminum step wedge 9) , HA, nickel step wedge and barium sulfate 10) . In previous studies based on panoramic radiographs, investigators evaluated mandibular morphology including the panoramic mandibular index (PMI), mandibular cortical M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 thickness (MCT), and the mandibular cortical index (MCI) [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Jaw bone densitometry studies were found to be far more accurate when including a fiduciary reference object, such as a step wedge, in the image. Some of these include an aluminum step wedge 9) , HA, nickel step wedge and barium sulfate 10) . In previous studies based on panoramic radiographs, investigators evaluated mandibular morphology including the panoramic mandibular index (PMI), mandibular cortical M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 thickness (MCT), and the mandibular cortical index (MCI) [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 29 descreveram que a densidade ós-sea alveolar normal é de 1.850 (g/cm 3 ), quando medida diretamente por um dispositivo simplificado associado ao filme periapical. Discutiram que, embora a absorciometria duo-energética por raios X (DXA) seja conhecida por alguns clínicos como padrão-ouro para análise de densidade ós-sea, seria de difícil acesso para os pacientes odontológicos.…”
Section: Pacienteunclassified
“…Entretanto, sugere-se que o padrão de exame inclua, além das áreas tradicionais femural e lombar, também a área mandibular. Observa-se, ainda, que o valor obtido por Yang et al 29 foi de 1.850g/cm 3 , praticamente o dobro do observado pelo presente estudo. Embora tenham calculado uma unidade cúbica em um exame bidimensional, mais trabalhos são necessários para detalhar essa diferença.…”
Section: Pacienteunclassified
See 2 more Smart Citations